Proof of Guilt : Barbara Graham and the Politics of Executing Women in America - Cairns, Kathleen A., 1946- (Book collections on Project MUSE., 2013)
Barbara Graham might have been a diabolical dame in a hard-boiled detective story - beautiful, sexy, and deadly. Charged alongside two male friends in the murder of an elderly widow during a botched robbery attempt, "Bloody Babs" became the third woman executed in California - after a 1953 trial that played out before standing-room-only crowds captured the imaginations of journalists, filmmakers, and death penalty opponents. Why, the author asks, of all the capital cases in the twentieth century, did Graham's have such political resonance and staying power? Leaving aside the question of guilt or innocence - debated to this day - this book examines how Graham's case became a touchstone in the ongoing debate over capital punishment. While prosecutors positioned the accused woman as a femme fatale, the media came to offer a counternarrative for Graham's life that highlighted her abusive and lonely beginnings. The author shows how Graham's case became crucial to the abolitionists of the time, who used instances of questionable guilt to raise awareness of the arbitrary and capricious nature of death penalty prosecutions. Critical in keeping capital punishment in the forefront of public consciousness until abolitionists homed in on a winning strategy, Graham's case illustrates the power of individual stories to shape wider perceptions and ultimately public policies.